Accessibility and Audio Enhancement in Broadcasting - Saefullah, Rifki; Jaizul, Alim (Communication In Research And Publications, 2025)
Audio accessibility in broadcasting is becoming increasingly important as technology advances and the need for inclusive services for people with disabilities increases. This study aims to analyze the implementation and key challenges in the adoption of four major audio accessibility technologies, namely Object-Based Audio (MPEG-H), AI-based dialogue enhancement (Dialog+), Auracast™ public broadcasting, and Smart TV interfaces with Text-to-Speech (TTS). The method used is secondary data analysis from various literature reports and international institutions, focusing on five countries: Germany, Japan, the United States, Indonesia, and Thailand. The results show that developed countries have implemented all four technologies comprehensively, while developing countries still face significant adoption gaps. The main barriers identified include device compatibility, high device prices, lack of user education, unprepared infrastructure, and limited local regulations. The findings emphasize that the successful implementation of audio accessibility technologies depends not only on technical readiness, but also on policy support, public-private partnerships, and public awareness. The comprehensive integration of MPEG-H, Dialog+, Auracast™, and TTS forms an inclusive broadcast ecosystem that can have a real impact on vulnerable groups. The study recommends a holistic approach to accelerate adoption and bridge the accessibility gap across countries.